Produkcja oraz rynek rzepaku na Ukrainie i jego perspektywy - Czerewko, Georgij; Dubnewycz, Jurij (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2014)
The paper presents the main aspects of rapeseed production and processing in Ukraine in the context of Ukraine’s joining EU. Current situation of rapeseed market and some aspects of exporting activity in this sphere were characterized. A set of possible directions of development of the situation in Ukraine including possible influences of UE’s policy in the sphere of alternative energy sources were presented, as well as changes of volumes of rape production. The paper also analyses the activity of Ukrainian government connected to the rapeseed production and processing, including avoidance of possible pathological Ukraine’s transformation into mere Europe’s raw materials’ supplier.